Employment deconcentration in european metropolitan areas. Market forces versus planning regulations. - (:unkn) unknown (Springer, 2007)
Die räumliche De-Konzentration wirtschaftlicher Betätigung, vornehmlich das Anwachsen suburbaner Verwaltungs- und Einkaufs und Vergnügungszentren ist für europäische Metropolen zu einem ernsten Problem geworden. Die vergleichende Untersuchung legt im Unterschied zu den meisten anderen Studien den geographischen Schwerpunkt auf Europa und befasst sich weniger mit der Suburbanisierung des Wohnens als mit der Suburbanisierung von Wirtschaft und Beschäftigung. Die acht Fallstudien arbeiten verschiedene Muster der Suburbanisierung der Arbeit heraus, untersuchen die Einflussfaktoren des Marktes und der lokalen Besonderheiten fragen nach den Wirkungen auf die Lebensqualität und mögliche Folgen für die Local Governance und die Kommunalpolitik.

Spatial deconcentration of economic activities, particularly the growth of suburban office, retail and entertainment concentrations, has become a prime concern in European metropolitan areas. This book provides a cross-national comparative perspective on employment deconcentration within selected metropolitan areas in Europe. Whereas most debate over urban sprawl and deconcentration is oriented towards the North American context, this book aims at a better understanding of this phenomenon in the European context, emphasizing the location of economic activities rather than residential patterns. It provides insights on whether different governance attributes produce particular forms of deconcentration versus the influence of market attributes and local specificities, also commenting on quality of life impacts and possible governance and policy implications of the deconcentration process. Introduction of a comparative framework is followed by eight case study chapters, three representing northern Europe, threethe southern European-Mediterranean region and two post-communist central Europe. Most chapters examine two metropolitan areas, usually a large one and a smaller one. The comparison reveals considerable variations in the magnitude, form, and process of employment deconcentration, only partly in line with expected influences of governance systems. Evidence does not fully confirm an anticipated distinction between Northern and Mediterranean Europe; the Czech Republic and Israel seem to diverge most from prevailing European trends.
Keywords: Arbeitsmarkt; Beschäftigung; Verdichtungsraum; Kommunalwirtschaft; Suburbanisierung; Büro; Verwaltung; Kommunalpolitik; Fallstudie; Vergleichsuntersuchung; Dekonzentration; Räumliche Verteilung; Local Governance